2019
DOI: 10.1002/dta.2589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the designer steroid Androsta‐3,5‐diene‐7,17‐dione in a dietary supplement

Abstract: A liquid chromatography‐mass spectrometry (LC–MS) screen for known anabolic‐androgenic steroids in a dietary supplement product marketed for “performance enhancement” detected an unknown compound having steroid‐like spectral characteristics. The compound was isolated using high performance liquid chromatography with ultraviolet detection (HPLC–UV) coupled with an analytical scale fraction collector. After the compound was isolated, it was then characterized using gas chromatography with simultaneous Fourier Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…The signal for arimistane was observed to be around 30% of 3‐acetyl‐7‐keto‐DHEA, and a very low signal (below 5%) of 7‐keto‐DHEA could be observed. This is in agreement with a recent publication on the analysis of 5‐en‐7‐keto structures . The three compounds were analyzed by IRMS without any additional derivatization and the δ 13 C values were − 32.2‰, −31.6‰, and − 32.0‰ for 3‐acetyl‐7‐keto‐DHEA, arimistane, and 7‐keto‐DHEA, respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The signal for arimistane was observed to be around 30% of 3‐acetyl‐7‐keto‐DHEA, and a very low signal (below 5%) of 7‐keto‐DHEA could be observed. This is in agreement with a recent publication on the analysis of 5‐en‐7‐keto structures . The three compounds were analyzed by IRMS without any additional derivatization and the δ 13 C values were − 32.2‰, −31.6‰, and − 32.0‰ for 3‐acetyl‐7‐keto‐DHEA, arimistane, and 7‐keto‐DHEA, respectively.…”
Section: Resultssupporting
confidence: 90%
“…No presence of arimistane nor any other impurity was observed in the capsule content. The results agree absolutely with the observation of Lorenz et al…”
Section: Methodssupporting
confidence: 92%
“…Designer steroids have also been found with increasing regularity, in products offered as all natural herbal supplements marketed for muscle mass and strength gain, as is the recently reported androsta-3,5-diene-7,17-dione, an aromatase inhibitor, which is included in the WADA banned list. Although little is currently known about the pharmacological effects and/or toxicity of this compound, its structure is similar to that of AAS which are known to cause significant health risks (Lorenz et al, 2019).…”
Section: Sports Supplements For Muscle Mass Gainmentioning
confidence: 99%
“…Additionally, studies have shown that DHEA supplementation does not improve erectile function (39). Numerous other compounds with steroid-like structures are not regulated and have been identified in dietary supplements marketed to "enhance performance," with one report finding that synthetic oral anabolic-androgenic steroids have been detected in up to 20% of performanceenhancing drugs sold legally over the counter (35,40,41). This is concerning, as many patients may not be aware of the potential health risks associated with exogenous steroid use, and even if they are, they may not be aware that these compounds are present in their oral supplements.…”
Section: Androgenic-anabolic and Designer Steroidsmentioning
confidence: 99%